An analysis of the sequence of an infectious clone of rice tungro bacilliform virus, a plant pararetrovirus. - Hay, J M (1991)
The nucleotide sequence of an infectious clone of rice tungro bacilliform virus (RTBV) DNA has been determined. The circular genome has 8002 bp and one strand contains four open reading frames (ORFs). One ORF is potentially capable of encoding a protein of 24 kD (P24) and has no initiation (ATG) codon. The other three ORFs potentially encode proteins of 12 kD, 194 kD and 46 kD (P12, P194, P46) respectively. The functions of P24, P12 and P46 are unknown. Comparative analyses with retroviruses and Commelina yellow mottle virus suggest that the 194 kD putative product is a polyprotein that is proteolytically cleaved to yield the virion coat protein, a protease and replicase (reverse transcriptase and RNase H) characteristic of retroelements. The DNA sequence reveals other features which strongly support our belief that RTBV is a pararetrovirus. These include sequences at the mapped positions of two discontinuities in the virion DNA which are complementary to tRNA metinit and purine-rich, and may be the priming sites for minus- and plus-strand DNA synthesis respectively. As the positions of likely transcriptional signals suggest, a full-length viral transcript is observed by northern analysis. The predicted folding of the 645 bp 5'-region of this RNA resembles that of caulimoviruses. Comparisons with other reverse transcribing elements are discussed.